Pathologic complete response to neoadjuvant imatinib of a gastric stromal tumor with concomitant mutations in KIT: A case report and literature review - Mariem Ben Rekaya; Feryel Ksontini; Linda Bel Haj Kacem; Farah Sassi; Emna Harigua‐Souiai; Ryma Boujneh; Ahmed H'mayada; Yosra Zaimi; Mouna Ayadi; Mediha Trabelsi; Ridha Mrad; Soumaya Rammeh (Clinical Case Reports, 2023)
Key clinical message We report the first case of pathologic complete response (pCR) to neoadjuvant imatinib in a gastric stromal tumor harboring KIT mutations in both exons 11 and 9. The significance of this co‐occurrence is unknown and might increase the responsiveness of gastrointestinal stromal tumors (GISTs) to imatinib. Abstract pCR of GIST to neoadjuvant imatinib is rare. We report a case of pCR to neoadjuvant imatinib in a gastric stromal tumor that harbored co‐occurrence of multiple KIT mutations in exons 11 and 9. This co‐occurrence in exons 9 and 11 is the first to be reported in the English literature.